2016
DOI: 10.1038/mtm.2016.52
|View full text |Cite
|
Sign up to set email alerts
|

Viral-mediated Ntf3 overexpression disrupts innervation and hearing in nondeafened guinea pig cochleae

Abstract: Synaptopathy in the cochlea occurs when the connection between inner hair cells and the auditory nerve is disrupted, leading to impaired hearing and nerve degeneration. Experiments using transgenic mice have shown that overexpression of NT3 by supporting cells repairs synaptopathy caused by overstimulation. To accomplish such therapy in the clinical setting, it would be necessary to activate the neurotrophin receptor on auditory neurons by other means. Here we test the outcome of NT3 overexpression using viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 39 publications
(45 reference statements)
0
17
1
Order By: Relevance
“…At this trauma-treatment interval, the neural degeneration likely includes only the synapse itself and the unmyelinated dendritic portion of the ANF within the organ of Corti (Liberman et al, 2015). Although some have reported that virally driven NT-3 overexpression can disrupt the normal innervation patterns in an undamaged cochlea (Lee et al, 2016), we have seen no signs of this in our experiments (Hashimoto et al, 2019). At longer traumatreatment intervals (i.e.…”
Section: Diagnosis and Treatment For Synaptopathy In Nihl And Arhlcontrasting
confidence: 48%
“…At this trauma-treatment interval, the neural degeneration likely includes only the synapse itself and the unmyelinated dendritic portion of the ANF within the organ of Corti (Liberman et al, 2015). Although some have reported that virally driven NT-3 overexpression can disrupt the normal innervation patterns in an undamaged cochlea (Lee et al, 2016), we have seen no signs of this in our experiments (Hashimoto et al, 2019). At longer traumatreatment intervals (i.e.…”
Section: Diagnosis and Treatment For Synaptopathy In Nihl And Arhlcontrasting
confidence: 48%
“…By contrast, despite its higher incidence and the economic consequences, there has been little success in preventing hearing loss caused by acoustic overexposure. Neurotrophin 3 [ 51 ], with the potential to resolve the synaptopathy caused by overstimulation, may be a candidate, but noninvasive methods to deliver the Nt3 gene to the cochlea before acoustic ototoxicity should be investigated before extensive gene therapy studies are conducted. Recently, inhibition of AMP-activated protein kinase (AMPK) by siRNA has shown a protective effect against acoustic overexposure in mouse [ 52 ], suggesting the alternative target for a therapeutic approach.…”
Section: Gene Therapy For Hearing Lossmentioning
confidence: 99%
“…If so, it will likely require support from other techniques, such as the damage-free injection of the required growth factors or inhibitors into the cochlea using, for example, a mini-osmotic pump. Innervating the cells with nerve fibers is also necessary for a positive functional outcome and might be feasible using neurotrophin gene therapy [ 51 , 88 90 ], which has already been widely tested in nerve regeneration and growth.…”
Section: Stem Cell Therapy For Hearing Lossmentioning
confidence: 99%
“…SN (sciatic nerve) injections of viral particles was followed using a previously prescribed procedure [7]. We have used V5 and FLAG tags due to their small size as tags, and data that have shown these tags lack effects in neurobehavioral studies [5, 6, 3840]. Preceding the SN exposure, 1.5 μl of 1.0E13 genome copies/ml of viral particles were injected into the sciatic nerve through a 35-gauge NanoFil needle using a NanoFil syringe (World Precision Instruments, Sarasota, FL).…”
Section: Methodsmentioning
confidence: 99%